The Effect of Agrochemicals and E-waste on Adverse Pregnancy Outcomes: A Methodological Review of Systematic Reviews - Ahmed, Shakil (My University, 2026)
Background: Exposure to environmental toxicants remains a critical global public health challenge, particularly during pregnancy, when maternal and fetal systems are uniquely vulnerable. Two major and increasingly prevalent sources of environmental contamination are agrochemicals, including pesticides and chemical fertilizers and electronic waste (e-waste), which commonly includes heavy metals, brominated flame retardants, and persistent organic pollutants. A growing body of research suggests that exposure to these substances may increase the risk of adverse pregnancy outcomes (APOs). However, the methodological quality and reporting standards of systematic reviews in this area are insufficient, which detracts from the reliability of existing conclusions. This uncertainty limits the reviews' effectiveness in informing policy decisions, clinical guidance, and risk communication. Objective: This methodological review aimed to systematically identify and evaluate the methodological and reporting quality of systematic reviews and meta-analyses examining the association between exposure to agrochemicals or e-waste and adverse pregnancy outcomes. The review further sought to compare statistical synthesis approaches used across meta-analytic reviews and identify methodological gaps to inform future research practice. Methods: This review followed the PRIOR (Preferred Reporting Items for Overviews of Reviews) reporting guideline. Two PROSPERO-registered protocols were developed a priori: one focused on agrochemical exposures (CRD42024533969) and one on e-waste exposures (CRD420250627366). Eight international bibliographic databases were searched without language or date restriction. Systematic reviews and meta-analyses reporting pregnancy-related clinical outcomes following exposure to agrochemicals or e-waste were eligible. Data extraction was performed independently by two reviewers. Methodological quality was assessed using AMSTAR-2. The completeness and transparency of search strategies were evaluated using the PRESS guideline and an operationalized reporting checklist developed by Norling et al. For reviews conducting meta-analysis, statistical methodology was assessed using a structured framework based on contemporary meta-analytic best practice. Results: A total of 39 systematic reviews were included: 27 on agrochemical exposures and 12 on e-waste-related toxicants. Across both exposure domains, the majority of reviews were rated as “critically low” quality according to AMSTAR-2, largely due to recurring critical weaknesses, including lack of prospective protocol registration, incomplete justification for excluded studies, and limited incorporation of risk-of-bias assessments into interpretation. Only a small proportion of reviews met high methodological standards. Evaluation of search strategy rigour showed moderate adherence to PRESS recommendations, although use of proximity operators, controlled vocabulary expansion, and search peer review were inconsistently applied. Reporting quality of search strategies also varied substantially, with incomplete documentation of databases, search dates, citation searching, and deduplication procedures in many reviews. Meta-analytic practices were heterogeneous, with frequent use of random-effects models but limited justification for model choice and variable assessment of heterogeneity and publication bias. Conclusions: This methodological review shows that most systematic reviews examining the impacts of agrochemical and e-waste exposure on adverse pregnancy outcomes have significant methodological and reporting limitations. These weaknesses reduce confidence in existing pooled estimates and limit the interpretability of findings for clinical, research, and policy decision-making. Strengthening future evidence synthesis in this field will require routine protocol registration, comprehensive and peer-reviewed search strategies, and standardized adverse pregnancy outcome definitions.
Keywords: Agrochemicals; E-waste; Pregnancy; Adverse Pregnancy outcomes; Maternal and fetal health